2019
DOI: 10.1098/rspb.2019.2398
|View full text |Cite
|
Sign up to set email alerts
|

Body mass and territorial defence strategy affect the territory size of odonate species

Abstract: The territory is a distinct mating place that a male defends against intruding conspecific males. The size of a territory varies between species and most of the variation between species has been found to scale allometrically with body mass. The variation that could not be explained by body mass has been explained with several variables such as habitat productivity, trophic level, locomotion strategy and thermoregulation. All previous interspecific comparative studies have been done on vertebrate species such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…We found that the length of larval period, primary larvae habitat, and hind wing length had phylogenetic signals, corroborating previous results (Aromaa et al, 2019; Ilvonen & Suhonen, 2016; Suarez‐Tovar et al, 2019). These findings indicate that intrinsic factors, such as these morphological and life history traits, are nonrandomly distributed in the phylogenetic tree of odonates (Waller & Svensson, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the length of larval period, primary larvae habitat, and hind wing length had phylogenetic signals, corroborating previous results (Aromaa et al, 2019; Ilvonen & Suhonen, 2016; Suarez‐Tovar et al, 2019). These findings indicate that intrinsic factors, such as these morphological and life history traits, are nonrandomly distributed in the phylogenetic tree of odonates (Waller & Svensson, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The mean hind wing length was calculated for each study species from the minimum and maximum values presented in the textbook “Dragonflies of Finland” (Karjalainen, 2010). Previous comparative studies have found that wing length and its morphological variations between species is a proxy for dispersal ability of odonates (Grewe et al, 2013; Hof et al, 2006; McCauley et al, 2014; Outomuro & Johansson, 2019; Rundle et al, 2007; Swaegers et al, 2014) and a species’ body size (Aromaa et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Accelerated development is linked to increased foraging and higher metabolic rates, which may increase energy requirements for maintenance at the expense of growth (Vannote & Sweeney, 1980), leading to early eclosion at smaller sizes (Hassall & Thompson, 2008; Johansson et al, 2001) and may occur even under food‐limited conditions (Plaistow & Siva‐Jothy, 1999). However, accelerating development to emerge at smaller size may entail fitness costs (De Block & Stoks, 2008a, 2008b) such as increased oxidative stress (that may pass to the next generation, De Block & Stoks, 2008b), reduced lifetime mating (Tüzün & Stoks, 2018) and breeding success (Aromaa et al, 2019; Rádai et al, 2020; Rowe & Ludwig, 1991) and ability to survive starvation (Stoks et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As lotic and lentic habitats could also plausibly differ in selective factors in the adult stage (e.g. temperature, habitat openness, degree of territoriality, predators [15,40,41]), future work should address how pressures on adults augment and/ or counteract the physiological conditions faced by larvae. Nonetheless, my findings support the hypothesis that inhabiting larval environments that are less suitable for prolonged growth and development can restrict the exaggeration of adult traits that are fixed at maturity.…”
Section: Macrommentioning
confidence: 99%
“…The Anisoptera-wide patterns could plausibly arise if lotic and lentic habitats differ, on average, in some other unknown selective pressures on adults (e.g. light [41], temperature [16] and predation [15]) or even on juveniles (e.g. via resource trade-offs over tyrosine with immune defense or cuticle integrity [12,13,42,43]; via other physiological costs of melanin production [14]).…”
Section: Macrommentioning
confidence: 99%